2020
DOI: 10.21203/rs.3.rs-117969/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Desulfovibrio and Pseudomonas Dominated Enriched Produced Water Reinforcing their Importance in Oilfields and Production Processes

Abstract: Enrichment based isolation methods and molecular identification were used to investigate the microbial communities in produced water obtained from Periquito (PQO) and Galo de Campinas (GC) onshore oilfields in Brazil. Produced water was enriched with Postgate B, Postgate C and Baars media and incubated. DNA was extracted, PCR amplified and16S rDNA fragments were sequenced using Illumina TruSEq. 4.2 million reads were analysed and deposited at the Sequence Read Archive at NCBI. No significative differences in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…Among the common metabolisms predicted in both samples, there was nitrate reduction and nitrogen and nitrate respiration, which play roles in N-cycling in the environment. Genera of bacteria responsible for nitrate metabolisms, such as Bacillus, Clostridium, and Citrobacter, were concurrently detected in the samples, and the metabolic predictions further validate their presence in the mine wastewater samples (Kisková et al, 2018;Tiburcio et al, 2020). Nitrification and Frontiers in Environmental Science frontiersin.org ammonium oxidation metabolic pathways both result in the formation of NO 3 − and were exclusively predicted in the Pt-SA sample that had the highest nitrate concentrations (177 mg/L), which strongly suggests that nitrifying bacteria converts NH 4 + and NO 2 − to NO 3 − (Spangler and Gilmour, 1966;Kim et al, 2005).…”
Section: Exploring the Microbial Diversities In The Wastewatersmentioning
confidence: 62%
“…Among the common metabolisms predicted in both samples, there was nitrate reduction and nitrogen and nitrate respiration, which play roles in N-cycling in the environment. Genera of bacteria responsible for nitrate metabolisms, such as Bacillus, Clostridium, and Citrobacter, were concurrently detected in the samples, and the metabolic predictions further validate their presence in the mine wastewater samples (Kisková et al, 2018;Tiburcio et al, 2020). Nitrification and Frontiers in Environmental Science frontiersin.org ammonium oxidation metabolic pathways both result in the formation of NO 3 − and were exclusively predicted in the Pt-SA sample that had the highest nitrate concentrations (177 mg/L), which strongly suggests that nitrifying bacteria converts NH 4 + and NO 2 − to NO 3 − (Spangler and Gilmour, 1966;Kim et al, 2005).…”
Section: Exploring the Microbial Diversities In The Wastewatersmentioning
confidence: 62%
“…Recent studies had identified several ways leading to the release of such elements into soil during shale gas exploitation process. For one thing, the disposal of untreated wastewater and leaching of poorly managed drilling wastes by rainwater o breakage of pipelines would directly generate release of heavy metals (Vidic et al, 2013;Cliffe et al 2020;Chen et al, 2020;Bonetti et al 2021;Tiburcio et al 2021). For another, the surface activities associated with shale gas development and migration of natural gas from deep to upper soil due to casing/cement failures could change mobilization of heavy metals (Brantley et al 2014;Bondu et al 2021;Zhou et al, 2023).…”
mentioning
confidence: 99%